Research on Temperature Control of Trough Solar Collector - Hui XU; Xin LI; Ershu XU (Zhongguo dianli)
In order to control the outlet temperature of the heat transfer fluid within reasonable range, it is necessary to develop a fast-response and effective control system for the outlet temperature in the parabolic trough solar plants. In this paper, a dynamic mathematical model of parabolic trough collector loop was established first, which took the solar field of a 1 MW solar parabolic trough power plant as the research object. And then an internal model controller (IMC) for the outlet temperature of the heat transfer fluid was proposed based on the developed mathematical model. Afterwards the IMC control system and PID control system were built respectively on the Simulink platform such that. the control effects under multiple disturbances were compared and analyzed accordingly. The results show that: under the disturbances of solar radiation, inlet temperature and ambient temperature, the IMC controller demonstrates better control effect with less time duration for control setting and less overshoot in contrast with the PID controller.